Iman Berakar dalam Keluarga dan Implikasinya pada Pendidikan Karakter Anak - Sitepanus Zebua (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2026)
This study aims to examine how faith rooted in the family has implications for children's character education. The family is the first and foremost environment in human life, where children begin to learn about life values, including faith, morals, and responsibility. In Christian families, parents play a crucial role in instilling and fostering faith through living examples, praying together, and participating in Church life. This study employed a qualitative research method with a descriptive approach. The analysis was conducted by reviewing various scientific sources and Church documents relevant to the research theme, such as Familiaris Consortio and Amoris Laetitia, which emphasize the role of the family as a